Influence of Blocking Effect and Energetic Disorder on Diffusion in One-dimensional Lattice - Lan, Mai Thị; Hong, Nguyen Van; Nhan, Nguyen Thu; Hue, Hoang Van (Communications in Physics, 2014)
The diffusion in one-dimensional disordered lattice with Gaussian distribution of site and transition energies has been studied by mean of kinetic Monte-Carlo simulation. We focus on investigating the influence of energetic disorders and diffusive particle density on diffusivity. In single-particle case, we used both analytical method and kinetic Monte-Carlo simulation to calculate the quantities that relate to diffusive behavior in disordered systems such as the mean time between two consecutive jumps, correlation factor and diffusion coefficient. The calculation shows a good agreement between analytical and simulation results for all disordered lattice types. In many-particle case, the blocking effect results in decreasing correlation factor F and average time \(τ _{jump}\) between two consecutive jumps. With increasing the number of particles, the diffusion coefficient \(D_{M}\) decreases for site-energy and transition-energy disordered lattices due to the F-effect affects stronger than \(τ\)-effect. Furthermore, the blocking effect almost is temperature independent for both lattices